2008
DOI: 10.4141/cjas07073
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding hay before fresh alfalfa on the occurrence of frothy bloat in cattle

Abstract: The effect of feeding hay before fresh alfalfa on the occurrence of frothy bloat in cattle. Can. J. Anim. Sci. 88: 29Á31. Alfalfa or orchardgrass hay was fed to cattle before feeding fresh alfalfa herbage at the vegetative to early bud stage of growth to observe the subsequent impact on bloat. Alfalfa hay supplements reduced the incidence of bloat by a third in one trial, but no effect was seen in a second trial. In contrast, supplements of orchardgrass hay reduced the occurrence of bloat by 90% in 2 yr of tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The risk of pasture bloat is negligible when cattle graze pastures with grass. Feeding corn silage or grass hay to cattle before turning them onto alfalfa pasture reduces the incidence of bloat substantially [ 113 , 114 ]. However, beef cattle and sheep are usually not (or not regularly) supplemented during the grazing season.…”
Section: Management Strategies To Reduce Bloat Incidence On Alfalfmentioning
confidence: 99%
“…The risk of pasture bloat is negligible when cattle graze pastures with grass. Feeding corn silage or grass hay to cattle before turning them onto alfalfa pasture reduces the incidence of bloat substantially [ 113 , 114 ]. However, beef cattle and sheep are usually not (or not regularly) supplemented during the grazing season.…”
Section: Management Strategies To Reduce Bloat Incidence On Alfalfmentioning
confidence: 99%
“…In a previous study it was observed that supplementation with orchardgrass hay was much more effective in reducing bloat than was alfalfa hay (Majak et al 2008). This suggests that the decrease in bloat in mixed pastures (Table 2) was more than an effect of forage dilution.…”
mentioning
confidence: 91%
“…Orchardgrass (Dactylis glomerata L.) has been previously shown to reduce bloat when it was a component of mechanically harvested alfalfa or when it was fed as a hay supplement before grazing alfalfa (Majak et al 2003(Majak et al , 2008. The objective of this trial was to determine if allowing cattle to graze monoculture strips of orchardgrass and alfalfa would minimize the risk of bloat.…”
mentioning
confidence: 99%